The Influence of Macroeconomic Factors on Residential Property Prices in Malaysia Before and During COVID-19 - Puji Isyanto; Siti Hafsah Zulkarnain; Abdol Samad Nawi (Binus Business Review, 2023)
The macroeconomic environment directly and significantly impacts a country’s economy. For example, residential property prices in Malaysia have steadily increased in recent years. It has become a significant issue during the COVID-19 pandemic since a home is one of the essential items for each living human being. The research identified a few macroeconomic factors, such as Gross Domestic Product (GDP), private consumption, government expenditure, and household saving which influenced Malaysian residential property prices. The research applied a regression model to analyse the data to encounter the uncertainty problem related to Beaver univariance analysis. All data were collected by the Department of Statistics Malaysia, the National Property Information Centre (NAPIC), The World Bank Data, and other data streams. Then, the research was tested using the time series method to predict and forecast the model. Based on the findings, the research shows that the distribution data for all variables are not normal. Overall, the variables are significant using the time series regression with the level of significance at 1%, 5%, and 10%. All variables tend to have a positive impact on residential property prices. The findings have significant policy consequences. Hence, it is critical to understand the pathways through which housing influences the economy to develop beneficial policies, as housing price declines are frequently cited as the primary constraint on household expenditure.